Relatório de estágio curricular supervisionado em medicina veterinária - clínica médica de pequenos animais - Almeida, Jaqueline Ferreira de (2016)
This report describes the activities developed during the Supervised Curricular Internship in Veterinary Medicine by the academic Jaqueline Ferreira de Almeida in the area of Small Animal Surgical Clinic, under the guidance of Prof. Dr. Maria Ligia de Arruda Mistieri. The internship was initially carried out at Savassi Zanetti Clínica Veterinária, under the supervision of Prof. Dr. Guilherme Savassi, from February 1st to March 4th, 2016, totaling 200 hours. From March 14 to April 29, 2016, the internship took place at the University Veterinary Hospital of the Federal University of Santa Maria, under the supervision of Prof. Mauricio Veloso Brun, totaling 280 hours. Making a total of 480 practical hours. The stages of internship, routine and monitored cases and the report of three cases of interest were described: 1) Peritoneal ventricle shunt in a dog with hydrocephalus secondary to cerebral neoplasia. 2) Reduction of hip dislocation using the ileofemoral suture technique. 3) Application of polypropylene mesh to correct diaphragmatic eventration.